The Effect of Student-Centred Methods and Techniques on Primary School Students' Mathematics Achievement: A Meta-Analysis Study - Ulum, Hakan; Tümkaya, Songül (Universitas Malikussaleh, Aceh Utara, Indonesia, 2022)
The purpose of this study was to synthesize experimental studies that explain the effect of student-centred methods and techniques used in primary school mathematics courses on academic achievement. Some certain criteria were selected and applied regarding the inclusion of primary study in the synthesis. As a result of qualitative systematic review, data of the study were obtained from 63 studies that meet the inclusion criteria. The reliability of the coding protocol in the study was procured in two stages by assessing the